Observing the behaviour of reinforced magnesium alloy with carbon-nanotube and lead under 976 m/s projectile impact / M.F. Abdullah ...[et al.] - Abdullah, M.F.; Abdullah, S.; Omar, M.Z.; Sajuri, Z.; Risby, M.S. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper presents the effects of reinforced magnesium alloy, AZ31B with carbon-nanotube (CNT) and lead (Pb), in terms of ballistic resistance. Magnesium alloys possess high energy absorption capability for impact resistance. However, its capability is limited and needs to be enhanced to resist ballistic impacts. The addition of a reinforcement material within the magnesium alloy, such as CNT or Pb, can improve impact resistance. This study is divided into two ballistic test methods, namely experiment and simulation. The samples involved are the original AZ31B and reinforced AZ31B with CNT and Pb. The projectile type used for ballistic testing was a 5.56 mm FMJ NATO at a velocity of 976 m/s and the thickness of the plate was 25 mm. The aim is to study the ability of the plate against the ballistic resistance. The ballistic experiment utilises a high speed camera, at 100,000 fps, to capture the impact occurring on the plate’s surface. A Cowper-Symonds model is used for the ballistic simulation and indicates the ballistic resistance of the reinforced AZ31B with increments of CNT and Pb. The velocity of the projectile penetrating through the plate was reduced by over 45% compared to the original AZ31B alloy. Reinforcement using CNT and Pb on AZ31B improved the ballistic resistance behaviour and therefore, this material is suitable for use on ballistic panels